URGENSI BIMBINGAN DAN KONSELING DI PANTI ASUHAN MUHAMMADIYAH KISARAN TIMUR - Liza Ulmi Widi Arnaz; Alfi Rahmi (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
The essence of guidance and counseling itself is to provide understanding, knowledge and skills to individuals in order to achieve optimal independence and potential. The development of guidance and counseling has been increasing rapidly to date not only in schools, but also in society, especially in social institutions, namely orphanages. This happens due to the development of an increasingly advanced world of technology, so orphanage children must have the insight and skills to deal with it. The purpose of this activity is to help and provide understanding to orphanage children regarding the difficulties they face both in the personal, social, learning, and recovery fields. Guidance and counseling services are carried out at the Kisaran Timur Muhammadiyah (daughter) orphanage. The type of research conducted is descriptive qualitative with data collection techniques by observation and interviews. The results of the study revealed that the need for guidance and counseling services in orphanages as a place to complain about their ups and downs in living a life that is certainly different from children in general, this is evidenced by the enthusiasm of those who are passionate about participating in guidance and counseling services.